Estudos sobre a síntese de 4H-Cromenos promovida pelo pentacloreto de nióbio para utilização como corantes sensibilizadores em células solares - Oshiro, Paula Beatriz [UNESP] (2015)
4H-chromete derivatives constitute an important class of natural products, and the the interest in its chemical occurs because of the numerous biological and pharmaceutical effects, as well their use a intermediates in the synthesis of numerous natural products and medicinal reagents. These derivatives can be obtained thorugh the multicomponent reactions (MCR). The MCR's occur between three or more reagents in one reaction step only, in the same pot. These reactions have time and energy saving. The niobium pentachloride is strong Lewis acid, which has wide applicabiblity in organic reactions, including multicomponent reactions. Among, the various methods of synthesis of 4H-chromene derivatives, developed in this work, the synthesis by multicomponent reactions between benzaldehyde derivatives, 3,5-dimethoxyphenol and methyl acetoacetate, using niobium pentachloride as the Lewis acid, is described. The reactions were carried out at room temperature, under inert atmosphere (N2), using dichloromethane anhydrous (CH2Cl2) as solvent with a reaction time of 72 hours. The obtained products were isolated by column chromatography on silica gel and subject to analysis of structural characterization, photophysics and photochemistry for a study of their potential use as sensitizing dyes of Gratzel photoelectrochemical devices. Our results show that niobium pentachloride is a good promoter to multicomponent reaction studied, obtaining high yields (62-91%)